In-vivo characterization of DALM in ulcerative colitis with high-resolution probe-based confocal laser endomicroscopy - Palma, Giovanni D De (Baishideng Publishing Group Co., Limited, 2011)
Recently, the use of confocal laser endomicroscopy (CLE) in the diagnosis of chronic ulcerative colitis (CUC) was reported. In this brief report we aimed to assess the application of probe-based CLE to characterize colonic mucosa and dysplasia in CUC. The study involved a patient presenting long-standing CUC. Confocal imaging of both the inflamed mucosa, a circumscribed lesion (dysplasia-associated lesional mass), and adjacent colonic mucosa are demonstrated and the correlation between the CLE and histological images. Inflamed mucosa and dysplasia showed specific alteration of crypt architecture, cellular infiltration, and vessel architecture with an excellent correlation between CLE and standard histological examination.